Functional Characterization of Anthocyanin Biosynthesis-Related Dihydroflavonol 4-reductase (DFR) Genes in Blueberries (Vaccinium corymbosum) - Yongyan Zhang; Sijian Guo; Zening Zhang; Ruide Li; Shitao Du; Siyi Hao; Chunzhen Cheng (Plants)
Dihydroflavonol 4-reductase (DFR) genes contribute greatly to anthocyanin biosynthesis in plants. Up to now, however, research on the DFR gene family and the key anthocyanin-related DFR members in blueberries (Vaccinium corymbosum) has been limited. In this study, we performed a genome-wide identification of the blueberry DFR gene family, identifying 36 VcDFR genes categorized into five subfamilies. Gene expression analysis showed that three Subfamily III members (VcDFR11/29/34) and four Subfamily V members (VcDFR4/7/30/33) are highly expressed in blueberry fruits, particularly at late ripening stages. Transient overexpression analysis in apple fruits verified the contributions of VcDFR11 and VcDFR30 to anthocyanin biosynthesis, with VcDFR11 showing better promoting effects. Blueberry fruit-based transient overexpression further confirmed the promoting effects of VcDFR11 on anthocyanin accumulation and the expression of anthocyanin-related structural genes (especially its downstream anthocyanindin synthase (ANS) and UDP-glucose: flavonoid 3-O-glycosyltransferase (UFGT) genes). The VcDFR11 promoter contains binding sites for both bHLH and MYB transcription factors (TFs). Consistently, yeast one-hybrid and dual-luciferase assays confirmed that anthocyanin-related VcMYB-1 and VcbHLHs can bind to and activate the VcDFR11 promoter. Furthermore, co-overexpressing VcMYB-1/VcbHLHs with VcDFR11 led to much higher anthocyanin accumulation than overexpressing VcDFR11 alone, indicating that these TFs positively regulate anthocyanin biosynthesis by upregulating VcDFR11. In summary, our study characterized the blueberry DFR gene family and demonstrated the role of VcDFR11 in anthocyanin biosynthesis.